2005
DOI: 10.1136/jnnp.2004.042432
|View full text |Cite
|
Sign up to set email alerts
|

DWI in transient global amnesia and TIA: proposal for an ischaemic origin of TGA

Abstract: There are conflicting reports concerning signal intensity changes in transient global amnesia (TGA) using diffusion weighted imaging (DWI). We prospectively analysed DWI signal intensity changes in TIA and TGA patients, and compared the clinical characteristics and risk factors of both groups. Using DWI and conventional T1 and T2 weighted turbo spin echo sequences, 28 patients with acute TGA (13 men, mean age 61.5 years) and 74 TIA patients (47 men, mean age 62.4 years) were studied within 48 hours after sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
91
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 23 publications
2
91
6
Order By: Relevance
“…This result concurred with the study by Sedlaczek et al, 9 in which the lesion-detection rate was 6% within 8 hours of onset and increased up to 84% at 48 hours after onset. The pathogenesis of TGA is uncertain, and various etiologic hypotheses have been proposed, including thromboembolism, 9,10 cerebral venous congestion induced by Valsalva-like activities, [18][19][20] and vasoconstriction caused by hyperventilation. 21 Whatever its etiology, several authors have suggested that delayed neuronal injury in the hippocampus is the cause of the delayed appearance of the lesions on DWI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result concurred with the study by Sedlaczek et al, 9 in which the lesion-detection rate was 6% within 8 hours of onset and increased up to 84% at 48 hours after onset. The pathogenesis of TGA is uncertain, and various etiologic hypotheses have been proposed, including thromboembolism, 9,10 cerebral venous congestion induced by Valsalva-like activities, [18][19][20] and vasoconstriction caused by hyperventilation. 21 Whatever its etiology, several authors have suggested that delayed neuronal injury in the hippocampus is the cause of the delayed appearance of the lesions on DWI.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent diffusion-weighted imaging (DWI) studies have indicated the presence of focal hyperintensities involving the hippocampus in TGA. [7][8][9][10][11] The lesions detected by DWI are small and punctate (1-3 mm) and located within the lateral portion of the hippocampus. 9,11,12 Since Strupp et al 13 first detected hyperintense lesions in the hippocampus in TGA by using DWI, the frequency of lesions detected on DWI has been reported in a range of 0%-84%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Some investigators have used diffusion-weighted imaging to examine the etiology of TGA, but the results have been controversial. 14 Several conditions have been reported to precipitate TGA: physical exertion, emotional stress, sexual intercourse, swimming in cold water, 1 coronary angiogra- 18 and reactivation of Epstein-Barr virus infection. 19 Transient global amnesia has been associated with ischemic events (acute infarction in the retrosplenium of the corpus callosum, 20 common carotid artery occlusion, 21 scleroderma, 22 meningioma, 23 antiphospholipid antibodies, 24 thalamic infarction, 25 dural arteriovenous fistula of the anterior cranial fossa, 26 and epileptic events meningioma), 27 and herpes simplex encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] The detection rate of TGA lesions on DWI has been reported as a wide range between 0%-84%. 6,7,10,16,17 These variable rates of lesion detection are attributable to different imaging parameters such as section thickness, b-value, and imaging timing from the onset of symptoms. High b-value (ie, 2000 -3000 seconds/mm 2 ), thin section thickness (ie, 3 mm), and imaging 48 -72 hours after the onset of symptoms increased lesion detectability of DWI.…”
mentioning
confidence: 99%